Comparing oncological outcomes of laparoscopic vs open radical nephroureterectomy for the treatment of upper tract urothelial carcinoma: A propensity score-matched analysis. Issue 1 (2nd January 2021) - Moschini, Marco; Zamboni, Stefania; Afferi, Luca; Pradere, Benjamin; Abufaraj, Mohammad; Soria, Francesco; D'Andrea, David; Roupret, Morgan; De la Taille, Alexandre; Simeone, Claudio; Mattei, Agostino; Mathieu, Romain; et al.
ABSTRACT: Objectives: To compare oncological outcomes of open (ORNU) and laparoscopic radical nephroureterectomy (LRNU) after controlling for preoperative patient-derived factors. Patients and methods: We evaluated a multi-institutional collaborative database composed of 3984 patients diagnosed with upper tract urothelial carcinoma (UTUC) treated with RNU between 2006 and 2018. To adjust for potential selection bias, propensity score matching adjusted for age, gender and American society Anesthesiology (ASA) score was performed with one ORNU patient matched to one LRNU patient. Uni- and multivariable Cox regression evaluating the risk of overall recurrence, cancer-specific mortality (CSM) and overall mortality (OM) in the overall population and after propensity matching were performed. Results: In total, 3984 patients underwent RNU, of these 3227 (81%) patients were treated with ORNU and 757 (19%) patients with LRNU. Within a median follow-up of 62 months, 1276 recurrences, 844 CSMs and 1128 OMs were recorded. On multivariable analyses, the LRNU approach was associated with an increased risk of overall recurrence (hazard ratio [HR] 1.26, 95% confidence interval [CI] 1.03–1.54; P = 0.02), but on the other hand LRNU was associated with a protective effect on CSM (HR 0.74, 95% CI 0.56–0.98; P = 0.04). After propensity matching analyses adjusted for age, gender and ASA score, 757 patients treated with LRNU and 757 patients treated with ORNU were available for the analyses. On multivariable Cox regression, LRNU vs ORNU was not associated with any difference in overall recurrence ( P = 0.08), CSM ( P = 0.1) or OM ( P = 0.9). Conclusion: Our present data suggest that even if the type of approach to RNU was associated with different survival outcomes considering the overall population, this difference vanished when adjusted for potential confounders in propensity matching analyses. Therefore, we found that LRNU is not inferior to the ORNU approach for the treatment of UTUC. Abbreviations: ASA: American Society of Anesthesiology; CIS: carcinoma in situ ; CSM: cancer-specific mortality; HR: hazard ratio; IQR: interquartile range; LN: lymph node; LNI: lymph node invasion; LVI: lymphovascular invasion; OM: overall mortality; pT: pathological tumour stage; RCT: randomised controlled trial; (L)(O)RNU: (laparoscopic) (open) radical nephroureterectomy; UTUC: upper tract urothelial carcinoma